Time Series And Data Envelopment Analysis On The Performance Efficiency Of Dmmmsu-South La Union Campus - Milagros Baldemor (Talenta Publisher, 2018)
This study entitled “Time Series and Data Envelopment Analysis (DEA) on the Performance Efficiency of DMMMSU-South La Union Campus” determined the performance of the Don Mariano Marcos Memorial State University -South La Union Campus, La Union, Philippines, a Level Four state university in the country, vis-à-vis its efficiency along the following performance indicators: Program Requirements, Research, Extension and Production for five (5) academic years 2009-2014. Furthermore, it determined the peer groups and weights of the DMUs (Decision Making Units – the different Colleges and Institutes), the virtual inputs/outputs or potential improvements of the colleges/institutes to be in the efficient frontier, the input and output slacks (input excesses and output shortfalls)needed in the different indicators and the best practices to be considered by the inefficient and weak efficient DMUs.The “best practice” in the frontier is the basis to calculate the adjustments necessary for the DMUs. Different indicators showed varied performance levels in the different academic years but there are best practices from the “efficient” DMUs which could be adapted by the “weak efficient” and “inefficient” ones.